Thematic exploration of educational research after the COVID pandemic through topic modelling (Journal of Applied Learning and Teaching, 2024)
The Journal of Applied Learning and Teaching is known for its focus on innovative practices in learning and teaching in higher education. In this study, we utilised BERTopic modelling to investigate trends and research within the journal. Our objective was to analyse thematic structures and identify emerging trends in a vast academic research corpus. BERTopic modelling enabled us to categorise academic texts into distinct topics, revealing underlying patterns and themes. Our analysis unveiled various topics, showcasing the journal’s interdisciplinary nature. Particularly, articles from January 2021 to December 2023 shed light on global trends in learning and teaching amidst significant changes in the post-COVID era. We identified 17 frequent topics, categorised into four major thematic groups: Technology and Digital Learning in Education, Healthcare and Clinical Training, Educational Strategies and Outcomes, and Pandemic-Driven Social and Compassion Aspects in Education. We examined these themes and presented the findings, highlighting challenges and opportunities in higher education. This comprehensive analysis serves as a roadmap for future research, guiding scholars and practitioners in advancing applied learning and teaching.